Victims' State War and Welfare in Austria, 1868-1925 - HSIA, KE-CHIN (Oxford University Press, 2022)
Victims' State is the first integrated account of how Imperial Austria and the successor Austrian Republic responded to the needs of citizen-soldiers and their families in the age of mass politics and the First World War. It shows that compulsory military service and war mobilization changed the mission of the Austrian state and citizens' understanding of what they were entitled to, thus showing how war victim welfare was central to shaping modern European welfare state.